Implicaciones de la potencial elevación del nivel del mar para la población costera de Tabasco, México - Gama Campillo, Lilia María; Díaz López, Hilda María; Collado Torres, Ricardo; Macías Valadez Treviño, María Elena; Mata Zayas, Ena Edith; Figueroa MahEng, José Manuel (El Colegio de México A.C., 2023)
Sea level rise has been accelerated due to global warming. The most threatened areas are small islands and coastal plains. Tabasco is located in a coastal flood plain. Using demographic information, coastal erosion values ​​and global sea level elevation data, the area and localities up to one meter above sea level (MASL) were identified. The results indicate that 55.58% of the state surface is within this range. In addition, the potential loss of territory could affect 76 localities, transforming the possible productive activities carried out.